Study Guide for use with financial Accounting - Libby Robert (Irwin/McGraw Hill, 2004)
Real accounting for today's students: Libby/ Libby/ Short wrote this book with the belief that financial accounting is an inherently interesting subject, but traditional textbooks are often not so interesting. In the Second Edition, the authors continue to bring the material to life offering the most real-world driven financial accounting text on the market. By writing the entire book based on real company annual reports, presenting material in a logical manner appropriate for introductory students, including active learning features, and further emphasizing the uses of accounting information, the Second Edition will continue to captivate instructors and students across the country. --This text refers to an out of print or unavailable edition of this title.